The foundations of modern macroeconomics - Heijdra, Ben J.; Ploeg, Frederick Van Der (Oxford ; New York : Oxford University Press, 2002)
The book deals with all major topics, summarizes the important approaches, and gives students a coherent angle on all aspects of macroeconomic thought. Each chapter deals with a separate area of macroeconomics, and each contains a summary section of key points and a further reading list, enabling the student to check what has been learnt and investigate further in others books.
Includes bibliographical references (p. [704]-733) and index
rpm; oif 15/07/14
Loan
Keywords: Macroeconomics